Analysis of (stressed) allocation risk in the aggregate credit portfolio of domestic banks - Peter Bednarek (Deutsche Bundesbank, 2021)
This paper analyses risks that arise from banks' credit portfolio composition and can be referred to collectively as allocation risk. That is, a potential increase in, or elevated levels of, allocation risk mean a larger exposure of banks to borrowers at the upper end of the risk distribution. In this sense, allocation risk does not concern a borrower's absolute risk, but rather its relative risk compared with other borrowers and whether banks have disproportionately high level of exposure to those borrowers. To analyse allocation risk, data on the financial statements of domestic, non-financial corporations are merged with data from the German credit register. The final sample covers a sizeable part of the banks' total exposure to the real economy, with nearly 4.9 million credit relationships between over 99,000 borrowers and 1,700 banks in a period spanning from 2000:Q1 to 2020:Q4. On the one hand, allocation risk based on measures that proxy borrowers' medium-term probability of default (debt overhang ratio and Altman Z-score) indicate elevated and even increasing levels of the risk in the banks' credit portfolio. On the other hand, those measures show, to some extent, resilience to scenarios stressing borrowers' debt and income levels. By contrast, allocation risk based on measures that proxy borrowers' short-term probability and immanent probability of reaching the stage of bankruptcy (interest coverage and cash ratios) indicate elevated risks in relative and absolute terms, respectively. The results for stressed allocation risk based on these two measures indicate vulnerabilities to scenarios stressing borrowers' interest expenses, i.e. higher interest rates.
Keywords: G21; G33; 330; allocation risk; bank lending; credit risk-taking; credit portfolio composition; real sector risk measures